Amalgamated tin mines of Nigeria Limited : twenty- nine year annual report and accounts for the year ended 31st March 1968 (London : Amalgamated tin mines of Nigeria Limited, 1968)
This is the Amalgamated tin mines general annual reports of the year 1968. The Chairman stated that the financial results for the year to 31st March, 1968, were unlikely to be more than marginal though they hope for improvement in the remaining six months.
ahz 18/04/2019
Loans
Keywords: Tin; Mining; Nigeria